Family relationships and personality disorder functioning styles in paranoid schizophrenia. (1st February 2021) - Jiang, Minggang; Shao, Xu; Zhang, Yan; Yan, Yupeng; Hu, Yuanyuan; Chen, Hong; Fan, Hongying; Wang, Wei
Abstract: Dysfunctional family relationships are prominent factors influencing personality development and psychiatric disorder progression, but the detailed relationships between personality disorders and family relationships in schizophrenia are less studied. In this study, we invited 92 paranoid schizophrenia patients and 76 healthy volunteers to answer the Family Relationship Questionnaire (FRQ) and the Parker Personality Measure (PERM). Compared to controls, patients scored higher on Paternal/ Maternal Abuse, but lower on General Attachment, Paternal Encouragement and Paternal/ Maternal Freedom Release. Patients also scored higher on all PERM styles except the Obsessive-Compulsive. In controls, Paternal Freedom Release predicted Paranoid (-), Maternal Abuse predicted Schizoid, General Attachment predicted Schizotypal (-), Histrionic (-) and Narcissistic (-), Paternal Abuse predicted Antisocial, and Maternal Freedom Release predicted Avoidant (-). While in patients, Paternal Abuse predicted Schizotypal, Antisocial, Borderline, Histrionic, Narcissistic, Dependent, and Passive-Aggressive. In conclusion, there were prominent family relationships and personality problems in schizophrenia, and the family relationships, especially paternal abuse, were associated with personality disorder functioning styles. Therefore, the intervention of paternal abuse in the early life might beneficial to reducing personality disorder traits in schizophrenia.